2012
DOI: 10.1186/1471-2148-12-204
|View full text |Cite
|
Sign up to set email alerts
|

Male-killing Wolbachia and mitochondrial selective sweep in a migratory African insect

Abstract: BackgroundNumerous recent studies have shown that resident symbiotic microorganisms of insects play a fundamental role in host ecology and evolution. The lepidopteran pest, African armyworm (Spodoptera exempta), is a highly migratory and destructive species found throughout sub-Saharan Africa, that can experience eruptive outbreaks within the space of a single generation, making predicting population dynamics and pest control forecasting extremely difficult. Three strains of Wolbachia have recently been identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…While we cannot rule out this possibility, it seems unlikely that this selective pressure has influenced the demographic history of each bat fly population sampled. Also, even in the case of Wolbachia infection in insects, high levels of migration may still be a more prominent factor reducing genetic differentiation in species with potential to disperse long distances [83]. Third, demographic factors, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…While we cannot rule out this possibility, it seems unlikely that this selective pressure has influenced the demographic history of each bat fly population sampled. Also, even in the case of Wolbachia infection in insects, high levels of migration may still be a more prominent factor reducing genetic differentiation in species with potential to disperse long distances [83]. Third, demographic factors, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A number of case studies have demonstrated that the spread of Wolbachia can indeed affect the mtDNA polymorphism (Turelli et al 1992;Solignac et al 1994;Ballard et al 1996;Jiggins 2003;Charlat et al 2009;Graham and Wilson 2012;Obbard et al 2012;Richardson et al 2012;Schuler et al 2016). Shoemaker (2004) also provided evidence for an elevated 70 non-synonymous substitution rate in an infected Drosophila species compared to its uninfected sister species, making Wolbachia and reduction in Ne a very plausible explanation.…”
mentioning
confidence: 99%
“…While molecular taxonomy may reveal cryptic lineages, the reliability of mtDNA for species delimitation has been criticised for various reasons (Rubinoff et al, 2006), including the persistence of genetic structure after resumption of gene flow due to lack of mtDNA recombination (for example, Lausen et al, 2008;Ruskey and Taylor, 2016), hybrid introgression (for example, Chen et al, 2009;MachadoSchiaffino et al, 2010) and selective sweeps caused by maternally inherited endosymbionts that can drive divergence and homogenisation across species (for example, Graham and Wilson, 2012;Xiao et al, 2012;Jäckel et al, 2013). These issues raise significant concerns when mtDNA is used in isolation, but they are likely to be resolved with further study of nuclear loci.…”
Section: Introductionmentioning
confidence: 99%